Pedagogical exploration of social studies teachers in integrating likurai to foster student’s nationalist character - Benu, Asti Yunita; Wiyanarti, Erlina; Sapriya; Ruhimat, Mamat; Darius Yonatan Nama (Harmoni Sosial: Jurnal Pendidikan IPS, 2026)
The study aim to explore the pedagogical strategies of social studies teacher in integrating likurai culture to strengthen student nationalistic character. This study uses a qualitative approach with a case study type. The subjects of the study were eighth-grade social studies teachers and the objects were pedagogical orientation, strategies, and implementation of likuari values in learning. Data were obtained through in-depth interviews, observation and documentation, then analyzed using the interactive model of Miles and Huberman with validity testing through source triangulation. The results of the study show that likuari integration encourages three main changes: increased student participation in discussions about national symbols; the emergence of historical reflection practices in project assignments; and increased attitudes of tolerance and togetherness as demonstrated in classroom observations. This study contributes to the development of social studies pedagogical studies by offering a likuari integration model as a strategy for developing national character. The findings regarding teacher strategies and student behavior indicators can be the basis for further research to develop an effective and contextual learning model.